Utilizing forest residue and different binding agent for biofuel pelletization - Yuganvarma, Ramasamy; Noor Asma Fazli, Abdul Samad; Suriyati, Saleh (AIP Publishing, 2025)
In this study, the effects of binding agents carboxymethyl cellulose (CMC) and palm oil mill effluent (POME) are discussed in relation to the characteristics of pellets made from sawdust of forestry residue, which includes Meranti (Shorea faguetiana) and Merbau (Intsia palembanica), with different composition ratios (100:0, 75:25 and 50:50). Initially, the raw materials were ground to reduce the sample size. The ground material was sieved, yielding samples with diameters ranging from 0.5 mm to 1.0 mm. Next, the pellet undergone the pelletization process in which the samples were exposed to a hot press machine with a range of compositions, binding agents and water. The samples were then subjected to a variety of tests, including a combustion test, a mechanical strength test to evaluate the durability of pellets, a moisture content analysis, a thermogravimetric analysis (TGA), and ash content. It was found that wood samples bound with CMC provide a higher mechanical strength and combustion rate than wood samples bound with POME. Furthermore, the incorporation of a greater binding agent and a wood sample composition ratio of 50:50 yields favourable outcomes for the physical characteristics of the pellet, including enhanced compression strength and combustion performance. In conclusion, wood samples bound with CMC in a composition ratio of 50:50 pellets have various benefits, including enhanced mechanical qualities, increased combustion effectiveness, and lower ash content.